Efektifitas Ekstrak Daun Sambung Nyawa Terhadap Pangasius sp Terinfeksi Bakteri Edwardsiella tarda - Elfrida Elfrida; Nawir Muhar; Abdullah Munzir; Amelia Sriwahyuni Lubis (University of Prof. Dr. Hazairin, SH, 2022)
This study aimed to analyze the effect of soaking the extracts of Gynura procumbens leaves with different concentrations on wound healing of catfish infected with Edwardsiella tarda bacteria. This research was conducted at the Wet Laboratory of the Fish Quarantine and Quality Control Agency of Padang, West Sumatra. This study used an experimental method with a completely randomized design (CRD) consisting of 3 treatments and 4 replications. The treatment of this research was the concentration of the Gynura procumbens leaves consisting of treatment P1 = 2000 ppm; treatment P2 = 3000 ppm and treatment P3 = 4000 ppm. Based on the analysis of variance, the concentration of the leaf extract had a significant effect on wound shrinkage. Duncan's follow-up test (DMRT) showed that the treatment was P1; P2; and P3 there are significant differences in each treatment. it was shown that Gynura procumbens leaf extract with different concentrations had no significant effect (p> 0.05) on the survival of catfish. The lowest survival rate in treatment P1 was 66.67%, and in treatment P2 and P3 was 100%. The best results were found in the P2 treatment of 80.20% on wound shrinkage and 100% on survival rate.